2015
DOI: 10.15361/1984-5529.2015v43n4p353-358
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade da abobrinha ‘Caserta’ em função do nitrogênio e gel hidrorretentor

Abstract: Resumo A cultura da abobrinha tem grande importância na economia olerícola, devido a sua produtividade elevada, grande aceitação pelos consumidores e rápido retorno financeiro. O objetivo deste trabalho foi avaliar a aplicação de gel hidrorretentor e doses de nitrogênio (N) sobre os componentes de produção e de produtividade da abobrinha cultivar Caserta. O experimento foi desenvolvido no período de abril a julho, no município de Aquidauana-MS. O delineamento experimental utilizado foi o de blocos casualizados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 7 publications
1
6
0
13
Order By: Relevance
“…. According to Trani and Raij (1996), the N content was within the range ideal for a cucumber crop, i.e., between 45 and 60 g kg -1 (leaf dry mass), indicating that the plants had an appropriate amount of N. The values found in this work are close to those reported by Pôrto et al (2014) for a cucumber crop and Azambuja et al (2015) and Pôrto et al (2011) for a zucchini crop. The N doses significantly influenced the relative chlorophyll index of the cucumber plants at 35 DAE, resulting in a value of 35 ( Fig 1B).…”
Section: Development and Production Componentssupporting
confidence: 84%
“…. According to Trani and Raij (1996), the N content was within the range ideal for a cucumber crop, i.e., between 45 and 60 g kg -1 (leaf dry mass), indicating that the plants had an appropriate amount of N. The values found in this work are close to those reported by Pôrto et al (2014) for a cucumber crop and Azambuja et al (2015) and Pôrto et al (2011) for a zucchini crop. The N doses significantly influenced the relative chlorophyll index of the cucumber plants at 35 DAE, resulting in a value of 35 ( Fig 1B).…”
Section: Development and Production Componentssupporting
confidence: 84%
“…Lima et al (2003) working with different irrigation depths and doses of hydroabsorbent polymer in the production of coffee seedlings, had similar results, as well as Fernandes et al (2015), in the growth of passion fruit seedlings, under the effect of irrigation depths and the use of hydrogel. Azambuja et al (2015) evaluating the use of hydrogel and nitrogen doses, also did not obtain a significant effect of the interaction of the factors studied for any of the evaluated variables.…”
Section: Resultsmentioning
confidence: 77%
“…For doses, the regression equation showed that under the dose of 169.41 g, plant height reached a maximum value of 20.32 cm, increase of 17.0% in relation to the dose 0 ( Figure 4B). Azambuja et al (2015) also found a higher plant height of Caserta zucchini plants when they performed the application of hydrogel on the occasion of sowing. The linear regression model was also the best fit for the variable yield, for the factor irrigation levels and for the solution dose factor, the appropriate model was the quadratic (Figure 5).…”
Section: Resultsmentioning
confidence: 83%
“…O nitrogênio é um nutriente que exerci um importante papel nos processos envolvidos no crescimento e desenvolvimento das plantas, alterando a relação fonte/dreno e, consequentemente, a distribuição de assimilados entre órgãos vegetativos e reprodutivos das plantas das famílias cucurbitáceas (BIANCHINI, 2013). Na abobrinha, o nitrogênio (N) está relacionado com a fotossíntese, respiração, desenvolvimento e atividade das raízes, crescimento e diferenciação celular (AZAMBUJA et al, 2015).…”
Section: Importância Do Nunclassified